A sentential subject asymmetry in English and its implications for complement selection - Alrenga, Peter (Syntax (Oxford, England), 2005)
.  In this article, I defend a particular solution to a long‐standing problem concerning the syntactic behavior of the verb seem—namely, its failure to take a sentential subject (*That the Giants lost the World Series seems). I show that this restriction follows straightforwardly if, following Koster (1978), sentential subjects are analyzed as topic phrases linked to a phonetically null DP in Spec,IP. I further suggest that this DP is an argument (not an expletive) and that it eventually undergoes A′‐movement, making sentential subject constructions a species of the null operator constructions discussed in Chomsky 1977. The analysis is supported by (i) active/passive asymmetries involving sentential subjects, (ii) agreement phenomena, (iii) restrictions on A′‐movement across sentential subjects, (iv) parallels between sentential subject and CP‐topicalization constructions, and (v) the distribution of embedded sentential subjects. The analysis also correctly predicts certain facts concerning the co‐occurrence of seem and sentential subjects in raising constructions. An interesting consequence of the analysis is that some form of idiosyncratic selection for DP complementation must be available within the lexicon, contrary to what has been suggested elsewhere.